Respon Laskar Jihad terhadap Pemikiran Islam Mazhab Ambon - Budianto, Muhammad Arief; Candra, Iga Ayu Intan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research aims to analyze Laskar Jihad's response to Mazhab Ambon's Islamic thought, particularly in the context of the dynamics of religious thought in Ambon. Uniquely, this research offers a new perspective on how Laskar Jihad, as a militant group, responds to the integration of local culture into Islamic teachings. In addition, it explores the application and acceptance of the teachings of the Ambon Mazhab of Islam in Ambon, as well as its impact on the social and religious life of the local community. Using a descriptive qualitative approach and a field study, the primary data sources in this research involved interviews with religious leaders, members of Laskar Jihad, and the Ambon community, and the secondary data sources were obtained through document analysis and related literature. The data obtained was analyzed and processed to draw accurate conclusions. The main findings of this study show that the conflict in Ambon, which was prone to be triggered by a lack of inter-religious tolerance, prompted scholars in Maluku to develop the Islamic Mazhab Ambon, an approach that integrates Islamic teachings with local cultural wisdom in order to create harmony in social life. However, the majority of Laskar Jihad members rejected the Ambon Mazhab of Islam because they believed it undermined the purity of Islamic teachings. This study also reveals how Laskar Jihad's conservative views can influence reconciliation and peacebuilding efforts in Ambon. By highlighting the social relevance of the Mazhab Ambon concept, which aims to promote tolerance, this study shows that the integration of local culture in Islamic teachings can be a strategy in building religious tolerance. Therefore, this study recommends strengthening interfaith dialog, multicultural education, as well as the active role of religious leaders in strengthening social cohesion in Ambon.